ATIM-15. SUSTAINED COMPLETE RADIOGRAPHIC RESPONSE AND PROLONGED SYSTEMIC IMMUNE ACTIVATION IN A PATIENT WITH MGMT UNMETHYLATED MIDLINE GLIOBLASTOMA RECEIVING CMV pp65-LAMP RNA-PULSED DENDRITIC CELL VACCINES. (11th November 2019) - Rahman, Maryam; Ghiaseddin, Ashley; Yegorov, Oleg; Yang, Changlin; Dechkovskaia, Anjelika; Tran, David; Massini, Tara; Kresak, Jesse; Mitchell, Duane
Abstract: BACKGROUND: We initiated a Phase 2, randomized, placebo-controlled, clinical trial evaluating the efficacy of autologous CMV pp65-LAMP RNA pulsed dendritic cell vaccines mixed with GM-CSF and administered during cycles of adjuvant dose-intensified temozolomide (ATTAC II, NCT02465268). STUDY OBJECTIVE: A patient with partially resected GBM experienced a sustained complete radiographic response after receiving five DC vaccines. Peripheral blood responses were characterized to examine possible immunologic biomarkers concordant with a sustained clinical response. METHODS: Patients with newly diagnosed glioblastoma undergoing surgical resection are eligible and randomized 2:1 to DC vaccine arms vs placebo (PBMCs in saline). DC vaccines consist of CMV pp65 RNA conjugated either to the full-length lysosomal associated membrane protein (LAMP) or to the short LAMP signal sequence. Patients undergo leukapheresis for DC generation prior to standard chemoradiation and receive cycle 1 of dose-intensified temozolomide (100 mg/m^2 x 21 days) before first three biweekly intradermal DC vaccines admixed with GM-CSF. Subsequent DC vaccines (total of 10) are given monthly with each diTMZ cycle with an intradermal tetanus-diphtheria booster given 6-24hrs before the third, fifth, seventh, and ninth DC vaccines. PBMCs and serum are collected for immune monitoring. RESULTS: A 58-year old white male with partially-resected, MGMT-unmethlyated, p53 mutant, H3.3 mutant, midline glioblastoma was enrolled on the ATTAC II study and experienced a complete radiographic response after the fifth DC vaccine that has been sustained > 10 months. Immune monitoring by Elispot, cytokine array, and single-cell RNA sequencing have revealed significant expansion of CMV pp65-specific immune responses, increased circulating IFNg, and marked systemic expansion of cytotoxic T cells and iNKT cells during vaccination. These responses were sustained through cycles of diTMZ despite profound lymphopenia. CONCLUSIONS: CMV pp65-LAMP RNA-pulsed DC vaccination was associated with profound immunologic and clinical response in a patient with MGMT unmethylated midline glioblastoma.